Ca2+ signals, NAADP and two‐pore channels: role in cellular differentiation. (June 2014) - Parrington, J.; Tunn, R.
Abstract Ca2+ signals regulate a wide range of physiological processes. Intracellular Ca2+ stores can be mobilized in response to extracellular stimuli via a range of signal transduction mechanisms, often involving recruitment of diffusible second messenger molecules. The Ca2+‐mobilizing messengers InsP3 and cADPR release Ca2+ from the endoplasmic reticulum via the InsP3 and ryanodine receptors, respectively, while a third messenger, NAADP, releases Ca2+ from acidic endosomes and lysosomes. Bidirectional communication between the endoplasmic reticulum (ER) and acidic organelles may have functional relevance for endolysosomal function as well as for the generation of Ca2+ signals. The two‐pore channels (TPCs) are currently strong candidates for being key components of NAADP‐regulated Ca2+ channels. Ca2+ signals have been shown to play important roles in differentiation; however, much remains to be established about the exact signalling mechanisms involved. The investigation of the role of NAADP and TPCs in differentiation is still at an early stage, but recent studies have suggested that they are important mediators of differentiation of neurones, skeletal muscle cells and osteoclasts. NAADP signals and TPCs have also been implicated in autophagy, an important process in differentiation. Further studies will be required to identify the precise mechanism of TPC action and their link with NAADP signalling, as well as relating this to their roles in differentiation and other key processes in the cell and organism.